PENGUATAN PARTISIPASI MASYARAKAT TRANSMIGRASI DI KAWASAN TRANSMIGRASI PULAU RUPAT MELALUI PENINGKATAN KAPASITAS - Nadia Irina Darmawan; Zulkarnain Zulkarnain; Ali Asfar (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2025)
This article discusses strategies for strengthening the participation of transmigrant communities through empowerment programs implemented by the Pekanbaru Transmigrant Community Training and Empowerment Center (BPPMT). The main focus of the activities is to increase community capacity through training in processing agricultural products based on local potential, such as bananas and cassava, involving transmigrant and local communities from Sungai Cingam Village and Makeruh Village. The training uses an andragogical approach and participatory methods, which have been proven to increase participants' knowledge by 83% and encourage social adaptation and collaboration between groups. The training results include food processing, packaging label creation, NIB and P-IRT management, and the formation of group business capital. The involvement of community institutions such as the PKK also strengthens women's participation and business sustainability. These findings indicate that empowerment based on contextual and collaborative training can be an effective strategy in increasing the participation and economic independence of transmigrant communities.